DEVELOPMENT AND CHARACTERIZATION OF ORO-DISPERSIBLE TABLETS OF METFORMIN HYDROCHLORIDE USING CAJANUS CAJAN STARCH AS A NATURAL SUPERDISINTEGRANT - DHIMAN, SONIA; BABBAR, RITCHU; SINGH, THAKUR GURJEET; ANAND, SHIVANGI; MANNAN, ASHI; ARORA, SANDEEP (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of the research work was to explore the use of Cajanus cajan (Pigeon pea) polysaccharide as a superdisintegrant. The novel superdisintegrant has been evaluated for its action by incorporating it into orodispersible tablets of Metformin Hydrochloride. Methods: Cajanus cajan starch was extracted from its seeds and superdisintegrant was developed by microwave modification of the extract. Various characterization tests such as gelatinization temperature, water absorption index, pH, and viscosity were used to identify the microwave-modified polysaccharide. The orodispersible tablets were made using a direct compression process employing varying concentrations of modified Cajanus cajan starch. Prepared tablets were tested for several pre and post-compression parameters and compared with a well-established synthetic superdisintegrant, sodium starch glycolate. The stability studies were conducted on an optimized formulation. Results: Fourier transform infrared spectroscopy study showed that the drug had no interactions with the microwave-modified Cajanus cajan starch. SEM confirmed that Cajanus cajan starch granules exhibited intact granular structure in oval shapes and smooth surfaces. After microwave modification, the Cajanus cajan starch component lost its granular structure, which further led to the generation of surface pores and internal channels, causing overall swelling responsible for superdisintegrant activity. The optimized formulation (ODF5) containing 15 % modified Cajanus cajan starch performed better in terms of wetting time (22.21 s), disintegration time (53.3 s), and in vitro drug release (92%), as compared to formulation prepared by synthetic superdisintegrant (ODF1). Conclusion: The present investigation concluded that modified Cajanus cajan starch has good potential as a superdisintegrant for formulating oro-dispersible tablets. Furthermore, modified Cajanus cajan starch is inexpensive, non-toxic and compatible in comparison with available synthetic superdisintegrants.